Construire sa masculinité en contexte migratoire. L’exemple des jeunes hommes latino-américains récemment arrivés en Suisse - Myrian Carbajal (Genre, Sexualité et Société)
On the basis of 15 in-depth interviews conducted with young Latin American men, recently arrived in Switzerland, this article analyses, by examining 3 situations, the construction of masculinities among these young men. Belonging to a minority and racialized group, the interviewees face a process of identity assignment, reducing them to the figures of the macho and the sexually successful Latino. In this context, however, the reference to the image of Latinos as “good lovers” allows these young men to reposition themselves as men and to put themselves in the best possible light in contrast with the sexuality of Swiss men. Indeed, the latter, even assimilated to a notion of fidelity, would be boring and not always able to offer sexual satisfaction to women. They affirm a masculinity based on the image of the Latino “good lover” which allows them to feel more valued in a society where they seek to create a place for themselves.